Models of Hfq interactions with small non-coding RNA in Gram-negative and Gram-positive bacteria - Watkins, Derrick; Arya, Dev (Frontiers in Cellular and Infection Microbiology, 2023)
Hfq is required by many Gram-negative bacteria to chaperone the interaction between small non-coding RNA (sRNA) and mRNA to facilitate annealing. Conversely and despite the presence of Hfq in many Gram-positive bacteria, sRNAs in Gram-positive bacteria bind the mRNA target independent of Hfq. Details provided by the Hfq structures from both Gram-negative and Gram-positive bacteria have demonstrated that despite a conserved global structure of the protein, variations of residues on the binding surfaces of Hfq results in the recognition of different RNA sequences as well as the ability of Hfq to facilitate the annealing of the sRNA to the mRNA target. Additionally, a subset of Gram-negative bacteria has an extended C-terminal Domain (CTD) that has been shown to affect the stability of the Hfq hexamer and increase the rate of release of the annealed sRNA-mRNA product. Here we review the structures of Hfq and biochemical data that have defined the interactions of the Gram-negative and Gram-positive homologues to highlight the similarities and differences in the interactions with RNA. These interactions provided a deeper understanding of the how Hfq functions to facilitate the annealing of sRNA-mRNA, the selectivity of the interactions with RNA, and the role of the CTD of Hfq in the interactions with sRNA.